2019
DOI: 10.1002/ana.25435
|View full text |Cite
|
Sign up to set email alerts
|

A case–control–family study of idiopathic rapid eye movement sleep behavior disorder

Abstract: Objective: To determine the familial aggregation of idiopathic rapid eye movement sleep behavior disorder (iRBD), neurodegenerative diseases, and related biomarkers. Methods: A total of 404 and 387 first-degree relatives of 102 patients with iRBD and of 89 controls were recruited, respectively. Among them, 204 and 208 relatives of patients and controls underwent face-to-face clinical assessment, whereas 97 and 75 relatives underwent further video-polysomnographic assessment, respectively. Results: Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 50 publications
1
32
1
Order By: Relevance
“…Only 1 patient had past history of benzodiazepine abuse, 2 patients of alcohol and one of cocaine abuse. Literature shows that one of the RBD-subgroups can be middle-aged women with autoimmune disease [ 11 ], but we did not find any association between RSWA and history of autoimmune disease in our patients’ cohort, as well as in positive perinatal history or family history of mental diseases [ 30 ]. Because other studies confirm several risk factors for RBD in general population [ 26 , 31 ], we hypothesized that it could reflect the epidemiological heterogeneity of RSWA/RBD.…”
Section: Discussioncontrasting
confidence: 65%
“…Only 1 patient had past history of benzodiazepine abuse, 2 patients of alcohol and one of cocaine abuse. Literature shows that one of the RBD-subgroups can be middle-aged women with autoimmune disease [ 11 ], but we did not find any association between RSWA and history of autoimmune disease in our patients’ cohort, as well as in positive perinatal history or family history of mental diseases [ 30 ]. Because other studies confirm several risk factors for RBD in general population [ 26 , 31 ], we hypothesized that it could reflect the epidemiological heterogeneity of RSWA/RBD.…”
Section: Discussioncontrasting
confidence: 65%
“…Patients with clinically diagnosed α‐synucleinopathies and patients with iRBD meeting the selection criteria were selected from a cohort of Hong Kong Chinese patients with iRBD (see Fig 1). Please refer to our previous studies regarding the profiles of this cohort 1,20 . Non‐rapid eye movement (REM) sleep behavior disorder (RBD) controls were recruited from the community 1 …”
Section: Methodsmentioning
confidence: 99%
“…Increasing studies have suggested idiopathic rapid eye movement (REM) sleep behavior disorder (iRBD) as a prodromal stage of α‐synucleinopathies, including Parkinson's disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA) 1,2 . iRBD is currently recognized as the strongest prodromal marker (likelihood ratio = 130) among 25 prodromal risk markers (likelihood ratio of other markers range from 1.2 to 43.3) in predicting the onset of prodromal PD 3 .…”
mentioning
confidence: 99%
“…The details about the vPSG assessment and the method of scoring the EMG activity level during REM sleep were previously reported 13,20,21 . Briefly, only chin EMG level was used to quantify the RSWA.…”
Section: Methodsmentioning
confidence: 99%
“…The details about the vPSG assessment and the method of scoring the EMG activity level during REM sleep were previously reported. 13,20,21 Briefly, only chin EMG level was used to quantify the RSWA. Tonic EMG activity was defined as an increase in amplitude at least twice the background muscle tone that lasted for at least 5 seconds.…”
Section: Vpsg Assessment and Electromyographic (Emg) Scoringmentioning
confidence: 99%